Pemanfaatan Tanaman Obat Keluarga (TOGA) sebagai Upaya Pencegahan Stunting di Dusun Barat Kokoq Desa Guntur Macam Kecamatan Gunung Sari Kabupaten Lombok Barat Tahun 2022 - Andy Susbandiyah Ifada; Sriama Muliani; Herni Sulastien; Erniawati Pujiningsih; Nur Radiah; Eva Zulfa; Nur Oktaviani; Muhammad Amrin Hakim; Winanda Sri Rahayu; Emi Laksmi Zahara (PT.Mantaya Idea Batara, 2022)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition. Stunting can be influenced by various factors, one of which is the nutritional status of pregnant women. The incidence of stunting in West Nusa Tenggara is 25.15% where West Lombok Regency has a very short category percentage of 8.64%, while the short category is 18.46%. Efforts to prevent stunting are carried out by providing counseling and inviting the public to use Family Medicinal Plants (TOGA), one of which is Moringa. These activities which were attended by pregnant women, cadres of posyandu, and mothers of infants and toddlers went smoothly and were enthusiastically welcomed by the community.